Differential Effects of Infection with a Babesia-Like Piroplasm, WA1, in Inbred Mice - Moro, Manuel H. (American Society for Microbiology, 1998)
A newly identified intraerythrocytic Babesia-like organism, WA1, and its relatives were recently shown to be infectious for humans in the western United States. The purpose of the present study was to determine the susceptibilities of selected mouse genotypes to WA1 infection in an attempt to develop a murine model of the human disease. Several mouse strains were inoculated intraperitoneally with various passages of WA1-parasitized erythrocytes. Parasitemia was evaluated by blood smears and by PCR with blood samples collected at various intervals after inoculation. Hematologic parameters were monitored in blood samples at all intervals. C57BL/6 and C57BL/10 mice exhibited mortality rates of <10%. BALB/cJ, CBAJ, and 129/J mice had higher peak parasitemias than did C57BL mice, with mortality rates of 40, 50, and 50%, respectively. A/J, AKR/N, C3H, and DBA/1J mice also had higher peak parasitemia and mortality rates (>95%). An F(1) cross of C57BL/6 (resistant) and C3H.RKK (susceptible) mice had a mortality rate similar to that of the resistant parental strain. Histopathology of BALB/cJ and C3H mice at 9 and 14 days after inoculation revealed erythrophagocytosis and deposition of an iron-negative pigment in multiple organs. Morbidly ill C3H mice at 14 days had severe pulmonary edema, hemoglobinuria, and glomerulonephritis.